Selective laser sintering of porcelain. Issue 2 (February 2018) - Danezan, A.; Delaizir, G.; Tessier-Doyen, N.; Gasgnier, G.; Gaillard, J.M.; Duport, P.; Nait-Ali, B.
Abstract: Selective Laser Sintering (SLS) technique is used to fabricate 3D porcelain products with complex shapes. Commercial powder has been studied and optimized in terms of morphology and particle size distribution in order to get a perfect powder layerwise which remains the critical step of such a technique. The influence of laser energy density (through the laser power and scan speed) and hatching space have been investigated to determine the optimized parameters that allow the greater densification of this complex multi-materials composed of kaolinite, quartz and potassium feldspar. The laser-sintered porcelain products which exhibit about 60% of porosity have been post-treated at 1350 °C under vacuum or air to further improve densification.